A synthetic ERFVII-dependent circuit in yeast sheds light on the regulation of early hypoxic responses of plants - Mikel Lavilla-Puerta; Yuming He; Luca Piccinini; Lorenzo Di Paco; Antonis Papachristodoulou; Francesco Licausi; Beatrice Giuntoli (Proceedings of the National Academy of Sciences, 2026)
Plants face hypoxic conditions either chronically, as particular tissues are characterized by fluctuating or stable low oxygen levels, or acutely, when flooded. In vascular plants, transcriptional adaptive responses to hypoxia are rapidly mounted by Ethylene Response Factors VII (ERFVIIs), regulated by Plant Cysteine Oxidases (PCOs) through the cysteine branch of the N-degron pathway (Cys-NDP) for oxygen sensing. However, this relatively simple regulatory circuit, consisting of both constitutively expressed as well as hypoxia-inducible ERFVIIs and PCOs, interacts with diverse signaling cues and pathways invoked by hypoxia. To understand the share of the PCO-mediated oxygen sensing mechanism in the production of hypoxia responses, we insulated the PCO/ERFVII circuit from Arabidopsis thaliana and adapted it to Saccharomyces cerevisiae . Using a reporter gene to monitor the output of the circuit allowed us to compare the speed and amplitude of response to hypoxia in the engineered yeast and the source organism. Hypoxia triggered ERFVII stabilization both in Arabidopsis and yeast, leading to a similarly fast transcriptional response that was however larger in plants. A simple hypoxia-inducible feedback loop improved the amplitude of response in yeast, demonstrating the importance of this regulation in the endogenous PCO/ERFVII circuit. Finally, computational modeling of the yeast circuit enabled us to identify promoter competition and presence of hypoxia-inducible PCOs as key parameters that shape early hypoxia responses in plant cells.